Class Struggle in Ralph Hosea Chaplin’s Poetry: A Marxist Perspective - Hanifah, Sekar; Santoso, Heri Dwi; Mulyadi, Dodi; Hardiyanti, Diana (Universitas Muhammadiyah Lampung, 2025)
Class struggle emerges due to the gap between two conflicting classes: the bourgeoisie (capital owners) and the proletariat (workers). The oppression and unjust distribution of rights lead the working class to fight for equality. This condition has been immortalized in poetry by poets as a reflection of social realities. This research aims to examine the application of Marxist theory in literature by analyzing class struggle in Ralph Hosea Chaplin’s poems,